(untitled) (Eurasian Scientific Herald, 2022)
In the 21st century, computers and the Internet have become indispensable companions of our lives - together they are an inexhaustible source of information, entertainment and communication. Today, scientists have not yet come to an unambiguous opinion about whether such increased attention should be paid to the problems of computer addiction. On the one hand, this hobby absorbs a person, forcing him to immerse himself in the virtual world to the detriment of communication, study, and sports. On the other hand, research data indicate that there comes a moment of satiety, a decrease in activity, unlike other forms of addictive realization